Endothelial and Epithelial Cell Transition to a Mesenchymal Phenotype Was Delineated by Nestin Expression. Issue 7 (July 2016) - Chabot, Andréanne; Hertig, Vanessa; Boscher, Elena; Nguyen, Quang Trinh; Boivin, Benoît; Chebli, Jasmine; Bissonnette, lyse; Villeneuve, Louis; Brochiero, Emmanuelle; Dupuis, jocelyn; Calderone, Angelino
Abstract : Cover : The cover image, by Angelino Calderone et al., is based on the Original Research Article Endothelial and Epithelial Cell Transition to a Mesenchymal Phenotype Was Delineated by Nestin Expression, DOI:10.1002/jcp.25257 .